New Fennoscandian Ground Motion Characterization Models - Vuorinen, Tommi (Helsingfors universitet, 2016)
The ground motion induced by an earthquake and its attenuation as a function of magnitude and distance can be estimated by using various ground motion prediction equations (GMPE). From a historical perspective, the Fennoscandian shield has been a seismically quiet area with a scarcity of strong earthquakes. This has made the area nominally an area with a low seismic hazard. The lack of quantative strong motion data in an area with low seismic hazard and the subsequent lack of advanced theoretical models of seismic response have hindered the developement of GMPEs for the region. Using more direct empirical methods, which do not depend on pre-existing models and simulations of Fennoscandian seismicity, and by taking advantage of the comparatively large Fennoscandian shield ground motion database two GMPEs targeted for the Fennoscandian shield area were created. The created GMPEs are based on an existing attenuation relationship that targets Eastern North America, which is a stable continental area similar to the Fennoscandian shield. The current and historical stage of relative seismic quietness was preceded by a considerably more active phase during and after the deglaciation of the Weichselian continental ice shelf ca. 9000 - 15000 years ago. There is ample geological evidence that this postglacial faulting caused some of the largest known earthquakes that have ever occurred in a stable continental area. The moment magnitudes of the largest postglacial earthquakes have been estimated to have been in excess of 8.0. The magnitude contrast between the geologically recent postglacial seismicity and the available Fennoscandian ground motion database, which consists mostly of low magnitude events, implies that an empirical method can not provide a GMPE capable of reliably estimating the ground motion induced by a potential large postglacial faulting event. It is unlikely that such an event could occur today, but not completely impossible. The two GMPEs presented here are based on a ground motion database consisting of ...